Perbedaan Perilaku Etis dan Tekanan Kerja Perspektif Gender dalam Audit Judgment Laporan Keuangan Historis dan Kompleksitas Tugas - Ardi Hamzah; Paramitha . (Universitas Kristen Maranatha, 2008)
This research purpose to examine the difference in matter ethic behaviour and work pressure at auditor when they conduct to complex audit assignment and they have to give the judgment about materiality. This research population is Public Accounting Oflice in Surabaya. This research use the questionnare, from 254 questionnare which sent that responded are 97 questionnare and which can be analysis are 54 quistionnaire. Data analysis use the program SPSS 12 for examine reliability, validity, and independent samples t-test. The research result indicate that there is diflerence that significant between auditor of male and female in matter ethic behaviour and work pressure. The other research result indicatethat married status, education level, working position, and work long there is not difference significant in matter ethic behaviour and work pressure.Keywords: ethic behaviour, work pressure, gender